Development and characterisation of poly-L-lactide-based foams fabricated through microwave-assisted compression moulding. (September 2019) - Singh, Manoj Kumar; Zafar, Sunny; Talha, Mohammad
Poly-L-lactide (PLLA) reinforced with nano-hydroxyapatite (HA) foams were fabricated using a novel method of microwave-assisted compression moulding. The microwave-assisted compression moulding is novel processing route of polymer-based composites, owing to its faster and uniform heating, better temperature control, which yields improved mechanical properties. Porosity in the PLLA+HA foams was introduced through porogen leaching route. The reinforcement in the form of nano-hydroxyapatite was added between 10 and 20 wt%. Porosity in the microwave processed foams was found in the range of 23–25%. The porosity in foams was observed to have homogeneously interconnected pores structure with narrower pore size distribution. The thermal behaviour of the developed foams was analysed using the thermogravimetric analysis and differential scanning calorimetry techniques. The glass transition temperature ( Tg ) and percentage crystallinity of the foams were assessed using the thermogravimetric analysis and differential scanning calorimetric curves. The maximum percentage crystallinity of 36.28% was obtained in case of PLLA + 15% HA foam. The mechanical characterisation of the microwave processed foams was carried out in terms of compressive and flexural behaviour. The foam with 20% HA reinforcement exhibited the maximum compressive strength (of the order of 21 MPa) and modulus of the order of 64.15 MPa. The foam with 10% reinforcement of HA exhibited maximum flexural strength of 59.32 MPa. The compressive strength of microwave processed foams was 10 times higher than the conventionally fabricated foams.